Espécies de Fusarium associadas a gramíneas forrageiras - Carmo, Filipe Sandin do (2017)
Grasses of the genera Brachiaria and Panicum are used as forages, intercrops, and as cover plants in non-tillage systems. Many species of the genus Fusarium are associated with grasses as endophytes or pathogens, including some known mycotoxin producers. This study aimed to answer the questions: (i.) what Fusarium species are associated with forage grasses? (ii.) Can forage grasses be a reservoir of species pathogenic to important crops? (iii.) Are there mycotoxin producers among the Fusarium species found on Brachiaria? The specific objectives were (i.) to investigate the composition of Fusarium species in association with forage grasses from different regions of Brazil, using molecular phylogeny and morphological markers; (ii.) to verify the production of mycotoxins by the species found. The 63 isolates obtained from seeds, leaves and stems were identified as F. verticillioides, F. proliferatum, F. thapsinum, F. fujikuroi, F. graminearum, F. equiseti, F. semitectum and F. chlamydosporum, using phylogenetic analyses of partial EF-1α and RPB2 gene regions and morphological markers. Fusarium mundagurra, a recently described species from Australia, was found for the second time during this study. Other three new phylogenetic lineages were found within the Fusarium fujikuroi species complex (FFSC), named Fusarium sp. 1, Fusarium sp. 2 and Fusarium “claudionori”. All species and lineages of the FFSC analyzed, including F. mundagurra, F. “claudionori” and Fusarium sp. 1, produced fumonisins and moniliformin in vitro. Brachiaria and Panicum grasses commonly harbor several Fusarium species and may act as reservoirs of pathogens of important to crops like maize. The mode of transmission of those species, their frequency in different host plants, geographical distribution, and the risk they pose as mycotoxin producers need further evaluations.